On some of convergence domains of multidimensional S-fractions with independent variables - Dmytryshyn, R.I. (Carpathian Mathematical Publications, 2019)
The convergence of multidimensional S-fractions with independent variables is investigated using the multidimensional generalization of the classical Worpitzky's criterion of convergence, the criterion of convergence of the branched continued fractions with independent variables, whose partial quotients are of the form q_i(k)^i_kq_i(k-1)^i_k-1(1-q_i(k-1))z_i(k) 1, and the convergence continuation theorem to extend the convergence, already known for a small domain (open connected set), to a larger domain. It is shown that the union of the intersections of the parabolic and circular domains is the domain of convergence of the multidimensional S-fraction with independent variables, and that the union of parabolic domains is the domain of convergence of the branched continued fraction with independent variables, reciprocal to it.